Health-related Quality of Life and Determinants of the Mental Dimension Among Tunisian Nurses in Public Hospitals - Bouzgarrou, Lamia; Merchaoui, Irtyah; Omrane, Amira; Ameur, Nada; Kammoun, Salma; Chaari, Neila (La Medicina del Lavoro, 2023)
Background: The health-related quality of life (HR-QoL) has been increasingly investigated in health sciences. The Objectives of this study are to evaluate the HR-QoL among nurses in Tunisian public hospitals and to identify the determinants of its mental dimension.Methods: A cross-sectional, bi-centric study was conducted within a representative sample of the 1,179 nurses assigned to 28 departments of two Tunisian public hospitals. A structured inquiry (socio-professional characteristics, occupational perceived workload) and validated questionnaires (SF12, Job Content Questionnaire of Karasek, Work Ability Index) have been completed.Results: Response rate was equal to 97.34%. The mean age of nurses was 42.60 ± 21 years. Nearly half of caregivers (49.07%) had a poor mental quality of life. The multivariate analysis concluded that mental HR-QoL was correlated with the female gender (0.010), obesity and the non-practice of regular physical activity (0.027), musculoskeletal diseases (